Solubility Based Identification of Green Solvents for Small Molecule Organic Solar Cells. (4th November 2013) - Burgués‐Ceballos, Ignasi; Machui, Florian; Min, Jie; Ameri, Tayebeh; Voigt, Monika M.; Luponosov, Yuriy N.; Ponomarenko, Sergei A.; Lacharmoise, Paul D.; Campoy‐Quiles, Mariano; Brabec, Christoph J.
<x xml:space="preserve">Abstract</x> Replacing halogenated solvents in the processing of organic solar cells by green solvents is a required step before the commercialization of this technology. With this purpose, some attempts have been made, although a general method is yet to be developed. Here, the potential of the Hansen solubility parameters (HSP) analysis for the design of green ink formulations for solution‐processed active layer in bulk heterojunction photovoltaic devices based on small molecules is demonstrated. The motivation of moving towards organic small molecules stems from their lower molecular weight and more definite structure which makes them more likely to be dissolved in a wider variety of organic solvents. In the first step, the HSP of selected active materials are determined, namely, the star‐shaped D‐π‐A tris{4‐[5′′‐(1, 1‐dicyanobut‐1‐en‐2‐yl)‐2, 2′‐bithiophen‐5‐yl]phenyl}amine N(Ph‐2T‐DCN‐Et)3 small molecule and fullerene derivative [6, 6]‐phenyl‐C71‐butyric acid methyl ester (PC70BM). Secondly, computer simulations based on HSP allow the prediction of suitable green solvents for this specific material system. The most promising green solvents, according to the simulations, are then used to fabricate solar cell devices using pristine solvents and two solvents mixtures. These devices show power conversion efficiencies around 3.6%, which are comparable to those obtained with halogenated solvents. This good performance is a result of the sufficient solubility achieved after a successful prediction of good (green) solvents.